Outbreak of Haff disease caused by consumption of crayfish (Procambarus clarkii) in nanjing, China. (4th May 2019) - Guo, Baofu; Xie, Guoxiang; Li, Xiaocheng; Jiang, Yun; Jin, Di; Zhou, Yonglin; Dai, Yue; Zhen, Shiqi; Sun, Guiju
Abstract: Context: This paper reports a detailed epidemiological investigation of a large Haff disease outbreak in Nanjing, China, including laboratory analysis of water, river sediment, and fish. Methods: Structured questionnaires were administered to all case-patients. An unmatched case-control study was conducted to identify the factors affecting the incidence of Haff disease. Thirteen samples of crayfish, together with four samples of water and four samples of sediment were collected and sent for laboratory analysis. Results: The disease onset of 494 patients occurred between 2 am on 30 June 2016 and 3 am on 29 August 2016. The median incubation time for onset of symptoms after crayfish ingestion was 7.1 hours (range: 1–20 hours). All patients presented with or developed local or diffuse myalgia. However, no kidney injury was observed. Serum creatinine kinase was elevated in all patients (mean: 4614 U/L, median: 2000 U/L, range: 81–55200 U/L). The average number of crayfish consumed by patients on the day of illness was 20 (2–80). The case-control study revealed that eating a large quantity of crayfish, drinking alcohol, and eating the crayfish head and/or intestines were associated with an increased risk of disease. Chemical analysis of crayfish, river water and sediment did not identify known or novel toxins including anticoccidiosis drugs, niclosamide, organophosphorus pesticides, and microcystins. Conclusion: An outbreak of Haff Disease was associated with consumption of crayfish from the Yangtze River and its surrounding water system. Eating a large quantity of crayfish, eating the head and/or intestines, and consuming alcohol with the crayfish were associated with the development of Haff Disease.